The arsenal of democracy : aircraft supply and the evolution of the Anglo-American alliance, 1938-1942 - Bailey, Gavin J. (Edinburgh studies in Anglo-American relations., 2013)
A critical re-examination of the conduct and outcome of Anglo-American wartime aircraft supply diplomacy. Through a series of case studies, Gavin J. Bailey reveals new details of how Britain used American aircraft and integrates this with broader British statecraft and strategy. He challenges conceptions that Britain was strategically reliant on the US and reveals a complicated, asymmetrical dependency between the wartime allies. Aircraft were at the heart of British supply diplomacy with the United States in the Second World War and were at the forefront of the Roosevelt administration's policy of aiding the Anglo-French alliance against Germany. They were the largest item in British purchasing in the US in 1940, a key consideration in the Lend-Lease of 1941 and a major component of several wartime conferences between Churchill and Roosevelt. Key Features. Challenges the basis of existing historiography in the area Adjusts the overall understanding of Anglo-American relations and their diplomacy